Al-Ṭaṣawwuf fī Indūnīsīyā: Dirāsah li Nuskhah al-Kitāb Maṭālib al-Sālikīn Ta’līf Yūsuf al-Makāsārī - Awis Kami (Studia Islamika, 1996)
Muhammad Yusuf al-Makasari (1627-1699) was one of the Muslim thinkers Nusantara (Indonesian) who lived around the leading 17th century. The other two are Nuruddin ar-Raniri (d. 1658) and as-Singkili Abdurrauf (1615-1693) derived from the Sultanate of Aceh .Yusuf al-Makasari has devoted his life to the propagation of Islam. He has focused his attention on the study of various fields, especially with respect to kalam (theology), tasawwuf (Sufism), and the shari'ah (Islamic law) and write no less than 23 books in Arabic.Matalib al-Salikin (MS) is one of the interesting work of Yusuf al-Makasari. Arable field which he wrestled in this book is tasawwuf, with the main thesis of the separation between tawhid impossible (oneness of God) , ma'rifah (divine knowledge), and worship (Rite). He maintains the view that if someone lost one of the elements of the integral, then it has fallen on an idolatrous attitude.DOI: 10.15408/sdi.v3i2.810